2015
DOI: 10.1097/bot.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Radiographic Healing

Abstract: The ICC for the modified RUST is slightly higher than the standard RUST in metadiaphyseal fractures and had substantial agreement. The ICC for the assessment of union was moderate agreement; however, definite union would be 10 and 13 with over 90% of reviewers assigning union. These are the first data-driven estimates of radiographic union for these scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(157 citation statements)
references
References 10 publications
2
126
5
1
Order By: Relevance
“…In fact Kim et al [36] revealed that the 16-year rate of survival of the components was 91% with bone allograft strut and the mean Harris Hip Score was 39 ± 10 points before revision and improved to 86 ± 14 points at 16-year follow-up ( p = 0.02) and the mean preoperative WOMAC score was 62 ± 29 (41–91) points and improved to 22 ± 19 (11–51) points at 16-year follow-up ( p = 0.003). Fractures treated with plate fixation are more rigid and do not form the same robust callus as those treated with intramedullary nails [37]. Furthermore, the presence of the plate with or without the bone allograft strut obscures the evaluation of the lateral cortex, and many reviewers commented on the difficulty in its scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact Kim et al [36] revealed that the 16-year rate of survival of the components was 91% with bone allograft strut and the mean Harris Hip Score was 39 ± 10 points before revision and improved to 86 ± 14 points at 16-year follow-up ( p = 0.02) and the mean preoperative WOMAC score was 62 ± 29 (41–91) points and improved to 22 ± 19 (11–51) points at 16-year follow-up ( p = 0.003). Fractures treated with plate fixation are more rigid and do not form the same robust callus as those treated with intramedullary nails [37]. Furthermore, the presence of the plate with or without the bone allograft strut obscures the evaluation of the lateral cortex, and many reviewers commented on the difficulty in its scoring.…”
Section: Discussionmentioning
confidence: 99%
“…This difficulty is reported in experimental work, where the intraclass correlation coefficient (between RUST and modified RUST) values of individual cortices that demonstrated the lowest agreement for the lateral cortex in plate fixation are seen. The goal of the modified RUST or RUS score described in many articles is to gain a greater range of scores during the crucial time of healing when callus was bridging [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Each callus, on the four cortices (two from antero-posterior and two from lateral views), was evaluated by four orthopedic surgeons blinded to the group. A bony union was defined when three of the four cortices were bridged and/or fracture lines disappeared completely [ 25 , 26 ]. Nonunion was defined if neither side of the callus was bridged in these views [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have been several types of methods for assessing the union rate while there is still no gold standard method. [ 9 , 10 ] In this study, we aimed to investigate the effects of associated factors like age, fracture level, accompanying fibular fractures and wound condition on healing by determining and comparing union scores of PTF.…”
Section: Introductionmentioning
confidence: 99%